Perencanaan Strategi Dari Aspek Marketing Mix UMKM Kuliner Kecamatan Wanea Dalam Masa Pandemi Covid-19 - Vilanri Gloria Mongdong; Leonardus Ricky Rengkung; Rine Kaunang (Sam Ratulangi University, 2022)
This study aims to identify strategic planning for Culinary MSMEs in Wanea District during the Covid-19 pandemic and analyze strategic planning for Culinary MSMEs in Wanea District during the Covid-19 pandemic.This research was made on February till march 2022. The analytical method used in this research is qualitative analysis with in-depth interviews and quantitative analysis using SWOT analysis. The results showed that the Culinary MSMEs in Wanea District carried out strategic planning from the marketing mix aspect (product, place, price, promotion, people, process, physical evidence, and based on the SWOT analysis the strategic planning position of the Culinary MSMEs in Wanea District was in Quadrant I (meeting between Strengths). and Opportunities) which shows that the Culinary MSMEs of Wanea District are in a favorable position because they have strengths and opportunities, namely by using online media as the best promotion during the pandemic and collaborating with delivery service applications so that products are more easily obtained by the public.